Euthanasia and Assisted Suicide. Pros and Cons regarding the Right to End Your Life with Dignity - M.M. Barsan; G. Dragu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The theme of euthanasia and assisted suicide calls for certain moral issues, but also for some legal issues. The two procedures are similar; however there are divergent elements, namely the fact that, in the case of euthanasia, the medic is the one who performs the act of killing, whereas in the case of assisted suicide, the patient plays the active role. Opinions on this issue are divergent and there are endless talks regarding these procedures, as EU countries do not have common laws on this matter. However, we believe that the most important argument which supports the right of a person to decide when to end his/her life is based on the principle of dignityand individual autonomy.